Evaluation of Factors Affecting Short-Term Clinical Outcome in Adult Patients with Tuberculous Meningitis - Adnan, Samee M; Akramul Azam; Kamrul Hassan; Shagor Deb Tapu; Md. Mubinul Huq Chowdhury; Aditi Das; Md. Hassanuzzaman; Md Mamunur Rashid; Anika Haque (Bangladesh Journal of Neuroscience, 2026)
Background: Tuberculous meningitis (TBM) is the most devastating form of Tuberculosis (TB) and is associated with high mortality. Objective: This study aimed to investigate the factors associated with short-term poor outcomes of TBM in patients admitted to a tertiary care hospital in Bangladesh. Methodology: This prospective analytical study included 42 patients with features of TBM, fulfilling the case definition criteria from the Department of Neurology and the Department of Medicine of Chattogram Medical College Hospital. The demographic, clinical, biochemical, and radiological data at baseline were collected, and clinical outcomes of patients were assessed by a modified Rankin Scale (MRS) and ‘two simple questions’ score at the time of discharge and three months from the time of diagnosis and initiation of treatment. The outcome was classified as good (survived and had modified mRS score of 0-2 and good or intermediate score in ‘two simple questions’ score) and poor (died or had mRS score> two and poor score in ‘two simple questions’ score). Results: The patients’ median (range) age was 37.5 (18-75) years, and 50% were male. Three months of mortality and poor outcome were observed in 19% and 40.5% of the patients. In univariate analysis, not vaccinated with Bacille Calmette Guerin (BCG) (p=0.019), lower GCS (p<0.001), altered sensorium (p=0.013), meningeal irritation signs (p=0.03), presence of hydrocephalus on brain imaging (p=0.047), low cerebrospinal fluid (CSF) glucose (p=0.016), increased CSF protein (p=0.023), and CSF pleocytosis (p=0.005), ESR (p=0.001), hyponatremia (p=0.015), definite TBM (P<0.001), and Stage III TBM (p=0.001) were significantly associated with short term poor outcome. On multivariate analysis, altered sensorium (p=0.032) and Stage III TBM (p=0.017) were independent predictors of short-term poor outcomes. Conclusions: TBM patients with poor outcomes were more likely to have altered mental status on admission and stage III disease than TBM patients with good outcomes.